2017
DOI: 10.20429/tag.2017.040101
|View full text |Cite
|
Sign up to set email alerts
|

Edge Colorings of K(m,n) with m+n-1 Colors Which Forbid Rainbow Cycles

Abstract: For positive integers m, n, the greatest number of colors that can appear in an edge coloring of K m,n which avoids rainbow cycles is m + n − 1. Here these colorings are constructively characterized; it turns out that these colorings can be encoded by certain vertex labelings of full binary trees with m + n leafs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…As for the year, it was identified that the first publication was carried out in 1995 ( 17 ) , two new publications in 2001 ( 20 ) , one more in 2003 ( 21 ) and another in 2004 ( 22 ) , three publications in 2005 ( 38 ) one more was found, four in 2020 ( 43 ) and one in 2022 ( 44 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the year, it was identified that the first publication was carried out in 1995 ( 17 ) , two new publications in 2001 ( 20 ) , one more in 2003 ( 21 ) and another in 2004 ( 22 ) , three publications in 2005 ( 38 ) one more was found, four in 2020 ( 43 ) and one in 2022 ( 44 ) .…”
Section: Resultsmentioning
confidence: 99%
“…The journals with the most publications on the subject were the newsletter On The Edge, with 10 publications ( 18 , 19 , 21 – 23 , 26 , 28 – 30 , 32 ) ; the Journal of Forensic Nursing, with three publications ( 24 , 34 , 40 ) and two publications in the Journal of Psychosocial Nursing and Mental Health ( 17 , 27 ) ( Chart 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We note here that JL-colorings of graphs only exist for connected graphs so this proposition implies that both A and Ā are connected and that the cut contains at least one edge, but further that the cut is an entire color class and that ϕ| A and ϕ| Ā have disjoint color sets. This was originally proved for complete graphs in [6], complete bipartite graphs in [11], and finally for complete multipartite graphs in [12]. Recently, it has been established for arbitrary JL-colored graphs in [8].…”
Section: The Structure Of Jl-coloringsmentioning
confidence: 97%
“…Recall that a JL-coloring ϕ is a rainbow cycle free (n − 1)-edge-coloring of a graph G with order n. There is a representation of JL-colorings as labeled binary trees which we will use to count RST's in a given JL-colored graph. The key to this approach, which has appeared in a series of papers of Johnson and collaborators (see [6,8,11,12]), is the following proposition: Proposition 1. Suppose ϕ is a JL-coloring of a connected graph G. Then there is a partition of V (G) into sets A and Ā, so that e(A, Ā), the set of edges between vertices in A and Ā, is monochromatic in ϕ, and both ϕ| A and ϕ| Ā are JL-colorings of the graphs induced on A and Ā respectively.…”
Section: The Structure Of Jl-coloringsmentioning
confidence: 99%
See 1 more Smart Citation